Pengaruh Kepemimpinan Dan Lingkungan Kerja Terhadap Motivasi Kerja Karyawan (Studi Kasus Pada Karyawan Konveksi Kota Yogyakarta) - Ramadhan, Muhammad Atma Jaya; Pahlevi, Reza Widhar (CV. Kurnia Grup, 2025)
This research is motivated by the importance of leadership and the work environment in shaping employee work motivation, particularly in the labor-intensive garment industry in Yogyakarta. The purpose of this study is to analyze the influence of leadership and the work environment on employee work motivation, both partially and simultaneously. This study employed a quantitative method with an explanatory approach and collected data through a closed-ended questionnaire. Respondents were selected using random sampling from the garment industry employee population in Yogyakarta, resulting in a sample of 54 respondents. Leadership and work environment variables were measured based on Human Resource Management (HRM) theory, which emphasizes the role of leaders and working conditions on individual behavior and motivation. Data were analyzed using multiple linear regression, preceded by validity, reliability, and classical assumption tests. The results indicate that leadership has a positive and significant effect on employee work motivation, as does the work environment. Simultaneously, both variables contribute 61.6% to the variation in work motivation, while the remaining 38.4% is influenced by factors outside the research model. These findings support HRM theory, which states that improving leadership quality and improving the work environment are effective strategies for enhancing employee motivation and performance.